2022
DOI: 10.1242/dev.200761
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion kinase-mediated signaling controls the onset of pancreatic cell differentiation

Abstract: Signals from the endothelium play a pivotal role in pancreatic lineage commitment. As such, the fate of the epithelial cells relies heavily on the spatiotemporal recruitment of the endothelial cells to the embryonic pancreas. While it is known that Vegf-A secreted by the epithelium recruits the endothelial cells to the specific domains within the developing pancreas, the mechanism that controls the timing for such recruitment is poorly understood. Here, we assessed the role of focal adhesion kinase (FAK) in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Of critical players in numerous cancer hallmarks, FAK has been identified as a hyperactive kinase that is associated with advanced-stage disease and clinically poor prognosis in diverse malignancies, [37][38][39][40][41] including HCC. 42,43 Accumulated evidence showed that FAK promotes tumorgenesis and metastasis via manipulating multiple cellular functions, including cell adhesion, 44 migration, 45 proliferation, 46 differentiation, 47 and survival, 21 through its kinase and scaffolding activities. 48,49 Our previous data demonstrated that FAK plays a crucial role in hepatocarcinogenesis in mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Of critical players in numerous cancer hallmarks, FAK has been identified as a hyperactive kinase that is associated with advanced-stage disease and clinically poor prognosis in diverse malignancies, [37][38][39][40][41] including HCC. 42,43 Accumulated evidence showed that FAK promotes tumorgenesis and metastasis via manipulating multiple cellular functions, including cell adhesion, 44 migration, 45 proliferation, 46 differentiation, 47 and survival, 21 through its kinase and scaffolding activities. 48,49 Our previous data demonstrated that FAK plays a crucial role in hepatocarcinogenesis in mouse models.…”
Section: Discussionmentioning
confidence: 99%